Reconstruction of the Trachea - Ch'ng, Sydney; Wong, Gerald L.; Clark, Jonathan R. (Journal of Reconstructive Microsurgery, 2014)
This article reviews established methods of autologous tracheal reconstruction, the various synthetic prostheses that have been used in clinical practice, and briefly describes the latest developments in stem cell tracheal bioengineering and allogeneic tracheal transplantation. Reconstruction of the trachea is challenging due to its part cervical part thoracic location, proximity to major vessels, variable blood supply, and its constant colonization with bacteria. In cases of limited resection, primary anastomosis, autologous patch grafts, local advancement rotation flaps, and locoregional cutaneous and muscle flaps will often suffice. In more extensive resections, complex composite microsurgical reconstruction with a radial forearm free flap with cartilage grafts for skeletal support has proven to be viable and reliable. Synthetic tracheal prostheses, solid as well as porous, have been trialed with disappointing results. Infection, dislodgement, migration, and obstruction are not uncommon. Reconstruction with the cadaveric tracheal allografts and aortic allografts continue to be fraught with complications, specifically graft infections. Tracheal bioengineering and tracheal allotransplantation have emerged relatively recently. Despite early promising results, long-term outcome data on these new techniques are still lacking.
Keywords: trachea; autologous; prosthesis; bioengineering; transplantation